INTEGRASI PASAR PRODUSEN DAN KONSUMEN DAGING AYAM BROILER DI INDONESIA - Rudy Julianto; Ahmad Zainuddin; Titin Agustina; Rena Yunita Rahman; Tiffany Rahma Abdillah (Fakultas Pertanian Universitas Mataram, 2026)
Broiler chickens are a type of poultry that supports economic growth in Indonesia. This study has two main objectives: first, to determine whether the integration of the broiler chicken meat market between producer and consumer markets in Indonesia is strong or weak in the short and long term. Second, to determine the projected price of producers and consumers of broiler chicken meat in Indonesia from 2024 to 2026, whether it will increase or decrease. This study uses data on producer and consumer prices of broiler chicken meat in Indonesia obtained from secondary data from the Badan Pusat Statistik (BPS). The data were analyzed using the IMC (Index of Market Connection) (market integration) and Holt-Winters Exponential Smoothing (price projection). The results of market integration indicate that market integration between producer and consumer markets of broiler chicken meat in Indonesia in the short term (IMC = 6.162) and long term (b2 = 0.406) is weak. In the long term, an increase in consumer prices of Rp. 1 is only passed on to producer prices by Rp. 0.406. Forecasting results indicate that producer and consumer prices for broiler chicken meat in Indonesia will increase from 2024 to 2026. Public awareness of the PHIPS application is needed to ensure real-time data is accessible to all farmers, providing a benchmark for increasing bargaining power when selling their produce.